2002
DOI: 10.1038/nature01200
|View full text |Cite|
|
Sign up to set email alerts
|

HIV-1 superinfection despite broad CD8+ T-cell responses containing replication of the primary virus

Abstract: Early treatment of acute HIV-1 infection followed by treatment interruptions has shown promise for enhancing immune control of infection. A subsequent loss of control, however, allows the correlates of protective immunity to be assessed. Here we show that sudden breakthrough of plasma viraemia occurred after prolonged immune containment in an individual infected with HIV-1 at a time when 25 distinct CD8+ T-cell epitopes in the viral proteins Gag, RT, Integrase, Env, Nef, Vpr, Vif and Rev were being targeted. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
213
0
5

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(226 citation statements)
references
References 25 publications
8
213
0
5
Order By: Relevance
“…Ein hoher Anteil der neutralisierenden Antikör-per ist gegen den V3-loop des gp120 gerichtet. Die Antikörper sind stammspezifisch und können die sich im Organismus eines Individuums ausbildenden Quasispezies von HIV dauerhaft nicht ausreichend eliminieren [25,77,78]. Unter dem Eliminationsdruck des Immunsystems werden Viren mit variablem V3-loop selektioniert.…”
Section: Hiv-2unclassified
“…Ein hoher Anteil der neutralisierenden Antikör-per ist gegen den V3-loop des gp120 gerichtet. Die Antikörper sind stammspezifisch und können die sich im Organismus eines Individuums ausbildenden Quasispezies von HIV dauerhaft nicht ausreichend eliminieren [25,77,78]. Unter dem Eliminationsdruck des Immunsystems werden Viren mit variablem V3-loop selektioniert.…”
Section: Hiv-2unclassified
“…Neither HIV-1-specific antibodies nor CD4+ T cell responses were investigated in this case, but might have contributed to the lack of control. At the same time, a case of HIV-1 superinfection involving two subtype B strains was also reported [9]. The individual enrolled in a structured treatment interruption trial after the initial infection, and developed a strong and broad HIV-1-specific CD8+ T cell response over time.…”
Section: Role Of T Cell Responses In Hiv-1 Superinfectionmentioning
confidence: 99%
“…While the neutralizing antibody response was found to be low, a cellular response of this magnitude and breath did not translate into protection against the second HIV-1 strain even though its sequence only differed by 12%. Thus, these and additional well-documented cases demonstrated that superinfection can occur in the context of limited HIV-1-specific cytotoxic T cell responses mostly directed against a single epitope [10,35], yet it is not prevented by the presence of broad responses to multiple epitopes [9,11,34,39].…”
Section: Role Of T Cell Responses In Hiv-1 Superinfectionmentioning
confidence: 99%
See 2 more Smart Citations